ChemInform Abstract: Ruthenium Carboxylate Complexes as Efficient Catalysts for the Addition of Carboxylic Acids to Propargylic Alcohols. Issue 44 (15th October 2015) - Jeschke, Janine; Gaebler, Christian; Korb, Marcus; Rueffer, Tobias; Lang, Heinrich
Abstract Newly synthesized ruthenium complexes are applied as catalysts in the addition of carboxylic acids to propargylic alcohols to give the corresponding β‐oxo esters in high yields even in air.